Racial Profiling Struktureller Rassismus und antirassistischer Widerstand - Wa Baile, Mohamed; Dankwa, Serena O.; Naguib, Tarek; Purtschert, Patricia; Schilliger, Sarah (Postcolonial Studies, 2019)
Racist police checks are part of everyday life in Europe. They make it dramatically visible who is not considered a fellow citizen. While much of the dominance society finds this racist practice normal, more and more people are no longer prepared to accept it without resistance. The volume brings together scientific, artistic and activist contributions to the social backgrounds and modes of action of racial profiling and the possibilities of intersectional anti-racist resistance. The focus is on Switzerland, supplemented by perspectives from authors who are familiar with the German context.